Integration of Religious Values and Local Wisdom: Strategy for Strengthening Local Traditions Towards the Self-Identity of the Community of Batu Bara District - Nilasari Siagian; Surono Zamroni; Andri Nurwandri (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to examine the religious values contained in the local wisdom of the Malay community in Batu Bara Regency through the traditions of Pesta Tapai, Mogang, and Mandi Belimau, which are held before the month of Ramadan. The research problem focuses on the form of religious values contained in these three traditions and their contribution to strengthening spirituality, social solidarity, and the preservation of local wisdom based on Islam. This study uses a qualitative method with an ethnographic approach. Data collection was carried out through field observations, in-depth interviews with traditional leaders, religious leaders, and community members, and documentation studies. The results show that Pesta Tapai functions as a means of strengthening religious values and empowering the community's economy; the Mogang tradition plays a role in strengthening social bonds and togetherness through kenduri activities; while Mandi Belimau is interpreted as a symbol of self-purification and spiritual readiness in welcoming the holy month of Ramadan. These three traditions not only function as customary practices, but also become a medium for internalizing Islamic values in the social life of the community. This research contributes to enriching the study of the integration of religious values and local wisdom, and emphasizes the importance of preserving cultural traditions as a means of strengthening religiosity, Malay-Islamic cultural identity, and passing on local values to the younger generation in Batu Bara Regency.